Hemodynamic Parameters in Students with Different Thresholds of Salt Sensitivity and Type of Autonomic Tone: An Observational Cohort Study - I. A. Chastoyedova (Кубанский научный медицинский вестник, 2023)
Background. Hemodynamic parameters are interrelated with both the threshold of salt sensitivity and the type of initial autonomic tone. Available data on such relationships are insufficient. Objective — to identify the hemodynamic parameters and features in students with different thresholds of salt sensitivity and types of autonomic tone.Methods. The study enrolled 174 second-year students of Kirov State Medical University, aged 18–23, who gave consent to the survey. The study was conducted over a period of four months and included two stages. At the first stage, all participants were evaluated for the threshold of salt sensitivity. According to the results, two groups were formed: group A — students with a normal threshold of salt sensitivity (n = 127); group B — students with a high threshold of salt sensitivity (n = 39). In the formed groups, a comparative analysis of hemodynamic parameters was carried out. At the second stage of the study, after assessing the initial autonomic tone, three groups were identified: group 1 (n = 40) — students with equilibrium of the sympathetic and parasympathetic systems (normotension); group 2 (n = 104) — students with dominating parasympathetic regulation of the heart rhythm (vagotonia); group 3 (n = 22) — students with dominating sympathetic regulation of the heart rhythm (sympathicotonia). Hemodynamic parameters were also studied in these groups. Statistical data processing was carried out using Statistica Advanced 10 for Windows RU. The differences between the comparison groups were assessed using parametric Student’s t-test and non-parametric Mann-Whitney U-test.Results. A high threshold of salt sensitivity was revealed in 23% of students. When comparing hemodynamic parameters in the groups, it was found that students with high thresholds of salt sensitivity had significantly higher values of systolic blood pressure, diastolic blood pressure, pulse pressure and average hemodynamic pressure than students with a low threshold. Differences in hemodynamics in students may be caused by differences in the original autonomic tone. Thus, students with vagotonia, if compared to those with normotension, have significantly lower values of heart rate, cardiac minute output, double product, and circulatory efficiency ratio, but a higher value of the peripheral vascular resistance. Students with sympathicotonia have statistically higher heart rate, cardiac minute output, and double product values.Conclusion. The assessment of hemodynamic parameters in healthy young people in relation to the threshold of salt sensitivity and the initial autonomic tone enables the risk factors for the development of hypertension to be assessed, prehypertension (high normal blood pressure) to be identified, and preventive programs aimed at reducing the number of diseases of the cardiovascular system to be developed.